(untitled) (International Journal of Biotechnology for Wellness Industries, 2015)
Based on a dynamic (i.e. time-dependent) one-dimensional approach, this work applied lattice Boltzmann method (LBM) to computationally model biospecific affinity chromatography (BAC). With governing equations expressed in lattice-based dimensionless form, LBM was implemented in D1Q2 lattice by assigning particle distribution functions to adsorbate concentration in both fluid and solid phases. The LBM simulator was firstly tested in view of a classic BAC work on lysozyme and the streaming step relating to adsorbate concentration in the solid-phase was suppressed from the LBM code with no loss of functionality. Expected behaviour of breakthrough curves was numerically reproduced and the influence of lattice-based dimensionless parameters was examined. The LBM simulator was next applied so as to assess lattice-based dimensionless parameters regarding an experimental BAC work on lipase.